Okazionalizem in vsemoč misli - Božovič, Miran (Filozofski vestnik, 2016)
The article considers the famous case history The Mind of a Mnemonist, written by A. R. Luria, of a patient who had a perfect memory. His persistent attempts to forget are considered against a background of Elsterian states that are essentially by-products: the absence of a mental object can never be brought about intentionally, since the very attempt to do so only entrenches the object whose absence is desired. In Malebranchian occasionalism, however, willing to forget does not necessarily mean “willing what cannot be willed”; before the Fall, Adam was still able directly to will the absence of a mental object: according to Malebranche, he was capable of erasing from his mind the ideas of sensible things at will. Hence, it is only through the first man’s sin that the attempt to will the absence of a mental object has become self-defeating. It is then suggested that the very logic of Elsterian states that are essentially by-products – as a rule, they slip away when we try to grasp them and fall into the hands of those who turn away from them – exactly corresponds to the logic mirrored in the conduct of Malebranche’s God, who consistently rebuffs those who are striving after him and rewards those who have turned their back on him.